The effect of creatine supplementation on seizure control in children under ketogenic diet: A pilot study. Issue 1 (2019) - Kalamitsou, Serafeia; Masino, Susan; Pavlou, Evangelos; Gogou, Maria; Katsanika, Irene; Papadopoulou-Legbelou, Kyriaki; Serdari, Aspasia; Spilioti, Martha; Evangeliou, Athanasios
No abstract available